Development of the Bestari Green Waste Bank: Integration of Creative Economy and Green Economy in Serang City - Julia Safitri; Fitri Normasari; Is Eka Herawati; Ratih Purnamasari; Putri Yudha Septiana; Jaka Pamungkas (EQUATOR SINAR AKADEMIA, 2026)
This study analyzes the development strategy of the Bestari Green Waste Bank in Serang City through the integration of the creative economy as the main driver of the transition to a green economy. Facing the urban waste management crisis, a paradigm shift is needed from the linear